Direct hydrothermal synthesis of highly ordered Sn-SBA-15 mesoporous materials - Shah, Pallavi; Ramaswamy, Arumugamangalam V.; Ramaswamy, Veda (Chemistry Letters, 2006)
Well-ordered Sn4+-incorporated mesoporous silica SBA-15 samples have been synthesized from tetraethyl orthosilicate (TEOS) and SnCl4 (Si/Sn = 114-15) using nonionic surfactants under a slightly higher pH medium (optimum H2O to HCl molar ratio) and characterized by XRD (an increase in lattice parameter), TEM (no SnO2 species) and UV-vis spectral (absorption at 211 nm) techniques to show that Sn4+ ions are in tetrahedral coordination in Sn-SBA-15.